Information flows within farmer networks and the implications for farmer-to-farmer extension: evidence from the Kenyan dairy sector - Morrison, Rosie; Cassar, Xandru G.G.N.A.; Duncan, Alan J.; Rao, E.J.O.; Barnes, Andrew P. (Informa UK Limited, 2025)
Purpose This article analyses the information flows within farmer networks to understand how farmer-to-farmer extension strategies can be made more effective.